Jewish Education and Jewish Identity in the Post-modern Era - Gross, Zehavit (Horyzonty Wychowania, 2017)
The author of the article analysed the profile of Jewish identityand education, indicating some essential problems and describingthe way they are being tackled today.As far as Jewish identity is concerned, Z. Gross distinguishedand depicted two separate standpoints, thus establishing twokinds of identity: substantive and constructive. She also describedthe diachronic and synchronic types of Jewish identitydiscourse, highlighting their implications for education.The educational system in Israel points to five fundamentalhistoric events (the establishment of the Zionist Movement, theHolocaust, the establishment of the State of Israel, The Six DayWar and the assassination of prime Minister Rabin) constitutinga significant factor of Jewish Zionist education, addressing themin school curricula of particular subjects. Also, it is important tocommemorate these events in educational processes in orderto nurture the Jewish memory and strengthen Jewish nationalsolidarity and identity despite the internal conflicts and fundamentalreservations. Hence, the ability to compartmentalize anddifferentiate between consensus and conflict in the educationalprocess is a salient feature of post-modern education. As to thesynchronic discourse, the educational system in Israel requirestransformation, since essentially no promoting forms have beenundertaken, only some sporadic activities done by few teacherspersonally aware and committed to this problem.The contemporary educational system in Israel, according toZ. Gross, faces three closely interconnected cardinal problems inthe ideological, social and administrative spheres. These difficultiesresult from the conflict between two Jewish civilizations andtraditions: the traditional and the modern. As a consequence, dramatictransformations in Jewish identity and Jewish education aretaking place.Therefore, these days the Israeli educational system needs tocerate a new, multicultural Jew, embodying the various identityconflicts that originated in historical and cultural processes. SuchJews are able to develop a dialectical approach towards the inherentconflicts, employing various identities as the basis of anidentity capable of facing the special challenges of traditionalsociety and adjusting itself gradually to ensure integration in the post-modern world.